Antibacterial Potential of SrBi2Ta2O9 Synthesized via Molten Salt Method - Izzah, Nuril Lailatul; Savira, Amalia; Ma’unatin, Anik; Safitri, Widya Nur; Hardian, Arie; Prasetyo, Anton (The Journal of Pure and Applied Chemistry Research, 2025)
One of the interesting properties of Aurivillius compounds is photocatalysts; therefore, they have the potential to be used as antibacterials. However, the study of the antibacterial properties of Aurivillius compounds is still very limited, therefore it’s important to conduct research on it’s properties. Our research aims to study the photocatalytic activity of SrBi2Ta2O9 compounds synthesized by molten salt method (using NaCl/KCl salt) as antibacterial. The diffractogram of the sample shows that the SrBi2Ta2O9 was successfully synthesized, but an impurity phase was formed as Bi2O3, Ta2O5, and SrBi2.83Ta5O15. The SEM images show that the morphological shape obtained is plate-like, which still has agglomeration with particle size distribution at range 20-80 μm. Plot tauc shows that the band gap energy of SrBi2Ta2O9 compounds is 2.8 and 3.06 eV, respectively. The antibacterial activity test results showed that the SrBi2Ta2O9 compound can inhibit staphylococcus bacterial growth under and without light radiation. It indicates that there are two possible mechanisms related to the inhibition of bacterial growth i.e: (a) photocatalysis, and (b) toxicity properties.